Russia's Annexation of Crimea and the Passage of Ships Through Kerch Strait: A Law of the Sea Perspective. (3rd July 2019) - Schatz, Valentin J.; Koval, Dmytro
: This article discusses potential Ukrainian rights of passage through Kerch Strait against the background of restrictions on passage imposed by Russia since the annexation of Crimea, taking into account the ongoing arbitral proceedings under Annex VII of the UN Convention on the Law of the Sea. The article addresses first the question of the status of Kerch Strait and the Sea of Azov under the international law of the sea. In a second step, the article deals with the issue of potential Ukrainian passage rights through Kerch Strait based on the legal status discussed in the first section as well as relevant bilateral treaties between Ukraine and Russia.